Towards Quantifying the Likelihood of Water Resource Impacts from Unconventional Gas Development. Issue 4 (25th September 2018) - Shanafield, Margaret; Cook, Peter G.; Simmons, Craig T.
Abstract: Gas production from unconventional reservoirs has led to widespread environmental concerns. Despite several excellent reviews of various potential impacts to water resources from unconventional gas production, no study has systematically and quantitatively assessed the potential for these impacts to occur. We use empirical evidence and numerical and analytical models to quantify the likelihood of surface water and groundwater contamination, and shallow aquifer depletion from unconventional gas developments. These likelihoods are not intended to be exact. They provide a starting point for comparing the probabilities of adverse impacts between types of water resources and pathways. This analysis provides much needed insight into what are "probable" rather than simply "possible" impacts. The results suggest that the most likely water resource impacts are surface water and groundwater contamination from spills at the well pad, which can be as high as 1 in 10 and 1 in 100 for each gas well, respectively. For wells that are hydraulically fractured, the likelihood of contamination due to inter‐aquifer leakage is 1 in 10 6 or lower (dependent on the separation distance between the production formation and the aquifer). For gas‐bearing formations that were initially over‐pressurized, the potential for contamination from inter‐aquifer leakage after production ceases could be as high as 1 in 400 where the separation between gas formation and shallow aquifer is 500 m, but will be much lower for greater separation distances (more characteristic of shale gas). Abstract : Article impact statement : Provides order of magnitude, quantitative estimates of the likelihood of water resource contamination due to unconventional gas development.